Theology and the Star Wars universe - Espinoza, Benjamin D. (Theology, religion, and pop culture, 2022)
"Theology and the Star Wars Universe is an engaging and enlightening foray into exploring the galaxy far, far away from a theological perspective. Written for an academic audience but accessible to fans of the franchise, the book will be an excellent addition to any collection"--